Poverty and Natural Resource Management in Pakistan (The Pakistan Development Review, 2007)
Pakistan is a country of contrasts, with diversified relief having majestic high mountain ranges snow-covered peaks, eternal glaciers, and the inter-mountain valleys in the north. Irrigated plains in the Indus basin contrast with stark deserts and rugged rocky plateaus in southwest Balochistan. The country is arid and semi-arid with substantial variation in temperature depending upon the topography and characterised by continental type of climate. Over the years since independence the natural resources of the country (land and water) have been harnessed which in turn made it possible to feed the growing population which more than quadrupled during the past sixty years. Construction of Tarbela and Mangla Dam facilitated the growth of irrigated agriculture and led the cropping intensity to peak. Sectors other than the agriculture also developed because of the backward and forward linkage of the agricultural growth thereby having an economy diversified and much less dependent on agriculture.